Event-by-Event Particle Ratio Fluctuations at LHC Energies - Shaista Khan; Bushra Ali; Anuj Chandra; Shakeel Ahmad (Advances in High Energy Physics)
A Monte Carlo study of identified particle ratio fluctuations at LHC energies is carried out in the framework of HIJING model using the fluctuation variable νdyn. The simulated events for Pb-Pb collisions at sNN=2.76 and 5.02 TeV and Xe-Xe collisions at sNN=5.44 TeV are analyzed. From this study, it is observed that the values of π,K, p,K, and π,p follow the similar trends of energy dependence as observed in the most central collision data by NA49, STAR, and ALICE experiments. It is also observed that νdyn for all the three combinations of particles for semicentral and central collisions, the model predicted values of νdynA,B for Pb-Pb collisions at sNN=2.76 TeV agree fairly well with those observed in the ALICE experiment. For peripheral collisions, however, the model predicted values of νdynπ,K are somewhat smaller, whereas for p,K and π,p it predicts larger values as compared to the corresponding experimental values. The possible reasons for the observed differences are discussed. The νdyn values scaled with charged particle density when plotted against Npart exhibit a flat behaviour, as expected from the independent particle emission sources. For p,K and π,p combinations, a departure from the flat trend is, however, observed in central collisions in the case of low pT window when the effect of jet quenching or resonances is considered. Furthermore, the study of νdynA,B dependence on particle density for various collision systems (including proton-proton collisions) suggests that at LHC energies νdyn values for a given particle pair are simply a function of charged particle density, irrespective of system size, beam energy, and collision centrality.